Genetic diversity of Panax vietnamensis var. langbianensis populations in Lam Vien plateau - Vietnam detected by inter simple sequence repeat (ISSR) markers - Ngoc Trieu, Le; Van Duy, Nong; Van Tien, Tran (Vietnam Journal of Biotechnology, 2020)
Panax vietnamensis var. langbianensis is a new variety from Lam Vien plateau of Vietnam. In this study, inter simple sequence repeat (ISSR) markers were employed to investigate the genetic diversity and variability of 115 individuals belonging to two naturally distributed populations of this variety, which classified by habitat. Genetic diversity at the taxon level was high (HeT = 0.284 and PPBT = 97.2 %). The result showed lightly higher genetic diversity in population in Lac Duong region (HeLD= 0.228 and PPBLD = 81.5 %) as compared to those located in Dam Rong region (HeDR= 0.213 and PPBDR = 79.4 %). The interpopulation gene differentiation was high (GST Total = 0.221) with the genetic distance among populations was DLD-DR = 0.191. Gene flow within populations was Nm = 0.8793. In Lac Duong population, the genetic diversity of older group (HeLD O = 0.233; PPBLD O = 77.1%) was higher than of younger group (HeLD Y = 0.214; PPBLD Y = 72.4 %) and the intergroup gene differentiation was GSTDL = 0.0205 with the genetic distance between these two group was DLD O-Y = 0.0061 showed the risk of reduction in genetic diversity. In Dam Rong population, the genetic diversity of older group (HeDR O = 0.204; PPBDR O = 75.2 %) was equal to younger group (HeDR Y = 0.209; PPBDR Y = 72.7 %) and the intergroup gene differentiation was GSTDR = 0.0304 with the genetic distance between them was DDR O-Y = 0.01393 showed the stability in genetic diversity. Data for genetic diversity and variation from this study can be used to further investigate and protect this variety for conservation and development purposes and for sustainable exploiting and use of these valuable natural resources.